Enterovirus D68-associated respiratory and neurological illness in Spain, 2014–2018 - Rubén González-Sanz; Irene Taravillo; Jordi Reina; Ana Navascués; Antonio Moreno-Docón; Maitane Aranzamendi; María Pilar Romero; Margarita del Cuerpo; Carmen Pérez-González; Sonia Pérez-Castro; Almudena Otero; María Cabrerizo (Emerging Microbes and Infections)
During 2014, enterovirus D68 (EV-D68) outbreaks were described globally, causing severe respiratory diseases in children and, in some cases, subsequent paralysis. In this study, the type characterization of enterovirus (EV) detected in respiratory illnesses and the epidemiology and clinical association of EV-D68 infections in Spain over a five-year period were described. A total of 546 EV-positive samples from hospitalized patients with respiratory infections were included. EV-D68 was the most frequently detected type (46.6%, 191/410 typed EV). Other EV from species A (25.1%), B (27.8%) and C (0.5%) were also identified. EV-D68 infections were more associated with bronchitis while EV-A/B types were more frequent in upper respiratory illness (p < 0.01). EV-D68 was also detected in patients with neurological symptoms (nine meningitis/meningoencephalitis and eight acute flaccid paralysis cases). Phylogenetic analysis of 3′-VP1 region showed most Spanish EV-D68 sequences from 2014 to 2016 belonged to subclades B2/B3, as other American and European strains circulating during the same period. However, those detected in 2017 and 2018 clustered to the emerged subclade D1. In summary, different EV can cause respiratory infections but EV-D68 was the most prevalent, with several strains circulating in Spain at least since 2014. Association between EV-D68 infection and neurological disease was also described.